THU0505 INTRINSIC AND EXTRINSIC B CELL DEFECT IN DADA2 PATIENTS. (June 2019) - Schena, Francesca; Penco, Federica; Volpi, Stefano; Pastorino, Claudia; Caorsi, Roberta; Kalli, Francesca; Fenoglio, Daniela; Salis, Annalisa; Bertoni, Arinna; Prigione, Ignazia; Bocca, Paola; Insalaco, Antonella; et al.
Abstract : Background: ADA2 Deficiency is an autoinflammatory disease characterized by systemic vasculopathy, strokes and mild immunodeficiency. The defect is due to a mutation in ADA2 gene. It regulates the catabolism of extracellular adenosine, which is an important regulator of Class Switch Recombination in B lymphocytes. Objectives: We addressed if ADA2 mutation affects directly B-cell function and the capacity of helper T cells to support B cells. Methods: 14 patients carrying LOF mutations in ADA2 were examined. We analyzed immunophenotype by flow cytometry. B cells isolated from DADA patients or HD have been cultured alone or in co-culture with CD4+ T cells and in vitro B cell proliferation has been evaluated by CFSE dilution, whereas B cell differentiation to Immunoglobulins secreting cells in response to TLR9 agonist and T cell help has been evaluated by ELISA assay. Results: Flow-cytometric analysis showed a significant reduction of switched memory B cells and of CD4+/CD8+ T cells. We identified an significant expansion of circulating Tfh cells in DADA2. Then we investigated a role of ADA2 in B cells: we found that it is expressed, secreted but the activity is strongly impaired in DADA2. We also addressed the interaction between B and T cells; we found that proliferation and differentiation of patients' B cells were not sustained from patient's T cells. Moreover DADA2 T cells showed an impairment in the IL21 production and a downregulation of CD40L. Conclusion: Our findings suggest that ADA2 mutation could affects directly B cell function and T cell help functions. References: [1] Zhou Q, et al. Early-onset stroke and vasculopathy associated with mutations in ADA2. N Engl J Med 2014 Mar 6;370(10):911-20. [2] Navon EP, et al. Mutant adenosine deaminase 2 in a polyarteritis nodosa vasculopathy. N Engl J Med 2014 Mar 6;370(10):921-31. [3] Schepp J, et al.Screening of 181 Patients with Antibody Deficiency for Deficiency of Adenosine Deaminase 2 sheds new lights on the disease in Adulthood. Arthritis and Rheum 2017 August; Vol. 69, 8:1689–1700. [4] Caorsi R, Monogenic polyarteritis: the lesson of ADA2 deficiency. Pediatr Rheumatol Online J 2016;14(1):51. [5] Caorsi R. et al.ADA2 deficiency (DADA2) as an unrecognised cause of early onset polyarteritis nodosa and stroke: a multicentre national study. Ann Rheum Dis 2017; 0:1-9. Disclosure of Interests: Francesca Schena: None declared, Federica Penco: None declared, Stefano Volpi: None declared, Claudia Pastorino: None declared, Roberta Caorsi: None declared, Francesca Kalli: None declared, Daniela Fenoglio: None declared, Annalisa Salis: None declared, Arinna Bertoni: None declared, Ignazia Prigione: None declared, Paola Bocca: None declared, Antonella Insalaco: None declared, Francesca Antonini: None declared, Alice Grossi: None declared, Gianluca Damonte: None declared, Isabella Ceccherini: None declared, Gilberto Filaci: None declared, Alberto Martini Consultant for: I do not have any conflict of interest to declare since starting from 1 March 2016 I became the Scientific Director of the G. Gaslini Hospital; therefore, my role does not allow me to render private consultancies resulting in personal income. I perform consultancy activities on behalf of the Gaslini Institute for the companies listed below: AbbVie, Biogen, Boehringer Ingelheim, Bristol-Myers Squibb, EMD Serono, Janssen, Novartis, Pfizer, R-Pharm. The money received for these activities are directly transferred to the Gaslini Institute's bank account. Before March 2016, I was the head of the Pediatric Rheumatology Department at the G. Gaslini Hospital, where the PRINTO Coordinating Centre is located. For the coordination activity of the PRINTO network, the Gaslini Hospital received contributions from the industries listed in this section. This money has been reinvested for the research activities of the hospital in fully independent manners besides any commitment with third parties., Elisabetta Traggiai Employee of: Novartis, Marco Gattorno Grant/research support from: MG has received unrestricted grants from Sobi and Novartis